HUBUNGAN ANTARA LAYANAN BIMBINGAN DAN KONSELING DENGAN KESULITAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA MADRASAH TSANAWIYAH NEGERI I MOJOKERTO - Miftakhul Djanah; Imam Mustai’n; Abdul Rouf; Dian Triana (Arsy : Jurnal Studi Islam, 2019)
This study aims to identify the effect of guidance and counseling services on student learning difficulties in Madrasah Tsanawiyah Negeri I Mojokerto.The hypothesis proposed is "there is a relationship between the influence of guidance and counseling services with learning difficulties for students of Madrasah Tsanawiyah Negeri I Mojokerto... While the magnitude of the relationship between guidance and counseling services and student learning difficulties is smaller than 0.50 (<50%).To test the truth of the hypothesis used instruments in the form of questionnaires distributed to all students as many as 32 students. The analytical model used is the Product Moment Determinations Correlation at the significance level = 0.05 for the first hypothesis and the Coefficient Determinations formula for the second hypothesis.From the analysis resulted that the relationship between guidance and counseling services at MTs Negeri I Mojokerto . in the "good" category. This is evidenced by the responses of the largest respondents with intervals of 35-47 as many as 21 respondents (56.7%). As for the learning difficulties of class VII and VIII MTs Negeri I Mojokerto students. in the "difficult" category. The conclusion is evidenced by the interval value of 35 - 47 as many as 20 respondents (59.4%). While the results of the latest research stated that guidance and counseling had a significant positive relationship with learning difficulties for grade VII and VIII students of MTs Negeri I Mojokerto .. This was evidenced by the value of r arithmetic (0.337) < r table (0.349) at a significant level of 0.05. Thus, the conclusion that the alternative hypothesis (Ha) I proposed reads "there is a relationship between guidance and counseling services with learning difficulties for grade VII and VIII students of MTs Negeri I Mojokerto. proven true, or "rejected". The magnitude of the relationship between student learning difficulties is smaller than 0.50 (50%) which is 11.3569%, the remaining 88.6431% is influenced by other factors, Hypothesis (Ha) II that the author proposes is proven true or "accepted".